2012
DOI: 10.1111/j.1567-1364.2011.00781.x
|View full text |Cite
|
Sign up to set email alerts
|

Systems biology of yeast cell death

Abstract: Programmed cell death (PCD) (including apoptosis) is an essential process, and many human diseases of high prevalence such as neurodegenerative diseases and cancer are associated with deregulations in the cell death pathways. Yeast Saccharomyces cerevisiae, a unicellular eukaryotic organism, shares with multicellular organisms (including humans) key components and regulators of the PCD machinery. In this article, we review the current state of knowledge about cell death networks, including the modeling approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 159 publications
(281 reference statements)
3
41
0
Order By: Relevance
“…ROS production has been implicated in the induction and regulation of the apoptotic pathway in yeast (8,18). DHR-123 is oxidized by intracellular ROS to the fluorescent chromophore rhodamine 123.…”
Section: Caspofungin Effects On Other Markers Of Apoptosis (I) Ros Pmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS production has been implicated in the induction and regulation of the apoptotic pathway in yeast (8,18). DHR-123 is oxidized by intracellular ROS to the fluorescent chromophore rhodamine 123.…”
Section: Caspofungin Effects On Other Markers Of Apoptosis (I) Ros Pmentioning
confidence: 99%
“…Indeed, apoptosis can be induced in C. albicans by oxidative stress (6), intracellular acidification, and the antifungal agent amphotericin B (7). Notably, C. albicans cells exhibit apoptotic markers that are similar to those of mammalian cells, including phosphatidylserine externalization, reactive oxygen species (ROS) accumulation, mitochondrial membrane potential dissipation, and DNA condensation and fragmentation (8). In this study, we evaluated the mechanisms of C. albicans cell death caused by caspofungin.…”
mentioning
confidence: 99%
“…This demands mechanisms of quality control and coordinated regulation, in order to avoid (or reduce) cellular stress that can result in reduced cell growth and protein secretion (1,2) or even apoptosis and cell death (3,4). Misfolded proteins are detected and removed via the endoplasmic reticulum (ER)-associated degradation (ERAD) pathway (5), the ubiquitin-proteasome system (UPS) (5), the autophagy pathway (6), or the unfolded protein response (UPR) pathway (7).…”
mentioning
confidence: 99%
“…Despite nearly a billion years of evolutionary divergence, recent estimates showed that a fifth of yeast genes have human disease orthologs lending support to functional discovery investigations using this model [92]. Moreover, thanks to amenability of S. cerevisiae to both classical and advanced molecular genetic techniques, to relatively simple, cheap and quick genetic and environmental manipulations, to the large knowledge base and data collections, high-throughput screening technologies and functional genomics that are not possible in humans [93][94][95], this organism has become a valuable and prevalent eukaryotic model organism to unravel complex and fundamental intracellular mechanisms underlying neurodegeneration [96][97][98][99][100][101][102][103][104].…”
Section: Yeast Models For Admentioning
confidence: 99%